Evidence for polymicrobial communities in explanted vascular filters and atheroma debris. (June 2017) - Ellis, Jeremy E.; Heuser, Richard; Missan, Dara S.; Martinez, Delyn; Heningburg, Avory; Shabilla, Matthew; Schwartz, Renata; Fry, Stephen
Abstract: Rationale: Microbial communities have been implicated in a variety of disease processes and have been intermittently observed in arterial disease; however, no comprehensive unbiased community analysis has been performed. We hypothesize that complex microbial communities may be involved in chronic vascular diseases as well and may be effectively characterized by molecular assays. Objective: The main objective is to survey vascular debris, atheroma, and vascular filters for polymicrobial communities consisting of prokaryotic and eukaryotic microbes, specifically eukaryotic microbes. Methods and results: We examined vascular aspirates of atheromatous debris or embolic protection filters in addition to matched peripheral blood samples, from fifteen patients, as well as three cadaveric coronary arteries from two separate patients, for microbial communities. General fluorescence microscopy by Höechst and ethidium bromide DNA stains, prokaryotic and eukaryotic community analysis by Next Generation DNA Sequencing (NGS), and a eukaryotic microbial 9 probe multiplexed quantitative PCR were used to detect and characterize the presence of putative polymicrobial communities. No prokaryotes were detected in peripheral blood; however, in 4 of 9 sequenced filters and in 2 of 7 sequenced atheroma debris samples, prokaryotic populations were identified. By DNA sequencing, eukaryotic microbes were detected in 4 of 15 blood samples, 5 of the 9 sequenced filters, and 3 of the 7 atheroma debris samples. The quantitative multiplex PCR detected sequences consistent with eukaryotic microbes in all 9 analyzed filter samples as well as 5 of the 7 atheroma debris samples. Microscopy reveals putative polymicrobial communities within filters and atheroma debris. The main contributing prokaryotic species in atheroma debris suggest a diverse and novel composition. Additionally, Funneliformis mosseae, an arbuscular mycorrhizal fungus in the Glomeraceae family, was detected in the coronary hard plaque from two patients. Well studied biofilm forming bacteria were not detectable in circulating peripheral blood and were not universally present in atheroma or filters. Analyses of the sequenced eukaryotes are consistent with a diverse of array poorly studied environmental eukaryotes. In summary, out of 15 patients, 6 exhibited molecular evidence of prokaryotes and 14 had molecular evidence of eukaryotic and/or polymicrobial communities in vivo, while 2 post-mortem coronary plaque samples displayed evidence of fungi. Conclusion: Prokaryotes are not consistently observed in atheroma debris or filter samples; however, detection of protozoa and fungi in these samples suggests that they may play a role in arterial vascular disease or atheroma formation. Highlights: The majority, 86%, of the atheroma debris and vascular filter samples exhibited microbial eukaryotic signatures via molecular testing. Funneliformis mosseae, an arbuscular mycorrhizal fungi, was detected in all cadaveric coronary arterial samples. Prokaryotic signatures were not a consistent finding in peripheral blood, atheroma debris, or vascular filter samples. Sequencing with 314 (samples 1-8) and 316 Chips (9-15). Prokaryotic (A) and eukaryotic (B) sequencing has reproducibility.